2016
DOI: 10.1007/s00401-016-1613-6
|View full text |Cite
|
Sign up to set email alerts
|

Ocular indicators of Alzheimer’s: exploring disease in the retina

Abstract: Although historically perceived as a disorder confined to the brain, our understanding of Alzheimer’s disease (AD) has expanded to include extra-cerebral manifestation, with mounting evidence of abnormalities in the eye. Among ocular tissues, the retina, a developmental outgrowth of the brain, is marked by an array of pathologies in patients suffering from AD, including nerve fiber layer thinning, degeneration of retinal ganglion cells, and changes to vascular parameters. While the hallmark pathological signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
215
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 212 publications
(232 citation statements)
references
References 188 publications
12
215
2
3
Order By: Relevance
“…In line with the above findings, numerous studies examining the retinas of sporadic and transgenic animal models of AD have reported Aβ deposits, vascular Aβ, pTau, and paired helical filament-tau (PHF-tau), often in association with RGC degeneration, local inflammation (i.e., microglial activation), and impairments of retinal structure and function (11,39,40,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57).…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…In line with the above findings, numerous studies examining the retinas of sporadic and transgenic animal models of AD have reported Aβ deposits, vascular Aβ, pTau, and paired helical filament-tau (PHF-tau), often in association with RGC degeneration, local inflammation (i.e., microglial activation), and impairments of retinal structure and function (11,39,40,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57).…”
Section: Introductionmentioning
confidence: 54%
“…A couple of studies that were unable to detect Aβ in the human AD retina analyzed horizontal cross sections spanning a narrow strip from the nasal to temporal quadrants (41,43), rather than screening large regions in flat mounts, thus limiting their analysis to regions that are largely spared of amyloid pathology in AD patients. Therefore, while Ho and colleagues (43) were unable to detect Aβ, p-tau, or α-synuclein in any ocular tissue of AD or Parkinson's disease (PD) patients, considerably more independent studies in fact reported the presence of Aβ deposits in the retina and lenses (11,39,40,42,51,83) as well as identified p-tau (41) and α-synuclein (84) in the retinas of AD and PD patients, respectively. Future studies should apply suitable techniques and comprehensive examination of flat-mount retinas to study additional pathological hallmarks of AD in the retina.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations